2020
DOI: 10.5194/acp-20-8017-2020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Aura-OMI QA4ECV NO<sub>2</sub> climate data records with ground-based DOAS networks: the role of measurement and comparison uncertainties

Abstract: Abstract. The QA4ECV (Quality Assurance for Essential Climate Variables) version 1.1 stratospheric and tropospheric NO2 vertical column density (VCD) climate data records (CDRs) from the OMI (Ozone Monitoring Instrument) satellite sensor are validated using NDACC (Network for the Detection of Atmospheric Composition Change) zenith-scattered light differential optical absorption spectroscopy (ZSL-DOAS) and multi-axis DOAS (MAX-DOAS) data as a reference. The QA4ECV OMI stratospheric VCDs have a small bia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…L3_NO 2 products were aggregated into decadal composites by averaging pixels with a cloud fraction lower than 40%, as suggested by Bauwens et al [7] Other studies by Boersma et al [23] and van Geffen et al [32] revealed that a threshold lower than 40% leads to more accurate NO 2 retrievals. However, Copernolle et al [33] claimed that low thresholds lead to the exclusion of aerosol and NO 2 -polluted Sentinel-5P scenes, which are essential from the perspective of the present study. Based on the decadal product, the following statistics were computed:…”
Section: Analysis Of the Sentinel-5 Tropospheric No 2 Column Densitymentioning
confidence: 79%
“…L3_NO 2 products were aggregated into decadal composites by averaging pixels with a cloud fraction lower than 40%, as suggested by Bauwens et al [7] Other studies by Boersma et al [23] and van Geffen et al [32] revealed that a threshold lower than 40% leads to more accurate NO 2 retrievals. However, Copernolle et al [33] claimed that low thresholds lead to the exclusion of aerosol and NO 2 -polluted Sentinel-5P scenes, which are essential from the perspective of the present study. Based on the decadal product, the following statistics were computed:…”
Section: Analysis Of the Sentinel-5 Tropospheric No 2 Column Densitymentioning
confidence: 79%
“…During the Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER-AQ) campaign over Baltimore in the US during July 2011, the NASA P-3B aircraft performed extensive profiling of the optical, chemical, and microphysical properties of aerosols (Crumeyrolle et al, 2014).…”
Section: Nasa Aircraft Campaign Datamentioning
confidence: 99%
“…Nevertheless, we did not apply any bias correction to any assimilated measurements in the reanalysis because of the difficulty in estimating the bias structure, including inter-measurement biases. To improve the temporal consistency, a detailed assessment of biases in individual retrievals (e.g., Compernolle, 2020) and between different retrieval products would be helpful, as already tested in the CAMS reanalysis (Inness et al, 2019).…”
Section: Assimilated Data Biases and Availabilitymentioning
confidence: 99%
“…Stratospheric NO 2 columns from STREAM differ by up to 3 × 10 14 molec/cm 2 as compared to results from data assimilation and other modified reference sector methods, within the general uncertainties of stratospheretroposphere separation (Beirle et al, 2016;Boersma et al, 2018). The STREAM stratospheric NO 2 columns show an average bias of 1 × 10 13 molec/cm 2 with respect to the ground-based zenith-scattered light differential optical absorption spectroscopy (ZSL-DOAS) measurements (Compernolle et al, 2020b).…”
Section: Stratosphere-troposphere Separationmentioning
confidence: 76%